[RETRACTED] Preparation and Characterization of Propolis (Trigona sp.) Extract-Loaded Chitosan Tripolyphosphate Nanoparticles - Sari, Puspita; Watiningsih, Lusi Karlina; Fachri, Boy Arief; Fauzi, Mukhammad; Sutarsi, Suratsi; Rumaisha-Zuhriansyah, Rayya (International Journal on Food, Agriculture and Natural Resources, 2024)
Propolis contains natural polyphenolic compounds with various biological activities, however, its application is limited due to low water solubility, instability in an aqueous medium, and low absorption rate in the body. The solution to overcome these drawbacks is to create nanoparticles of propolis extract. In this study, we encapsulated propolis extract in nanoparticles (propolis extract-loaded nanoparticles, PE-NP) using low/medium molecular weights of chitosan (LMW/MMW) and cross-linker sodium tripolyphosphate (TPP) by ionic/ionotropic gelation method as wall materials. We examined the physical characteristics (pH, turbidity, encapsulation efficiency, particle size, polydispersity index, zeta potential) and antioxidative properties of PE-NP prepared with the different molecular weights of chitosan, various concentrations of chitosan, and different volumes of propolis extracts. The resulting PE-NP revealed low encapsulation efficiency (23.937 - 41.192%) and pH in the range of 3.9 - 4.8. PE-NP also presented antioxidant capacity that was contributed by polyphenolic compounds in propolis extract. The suspension of PE-NP had a particle size of 350.000 - 488.280 nm with PDI values higher than 0.3 (heterogeneous dispersion), and positive zeta potential (39.340 - 48.200 mV), resulting in stable nanoparticles. The PE-NP produced can be used as functional ingredients in the food industry due to their antioxidative property.[This article has been officially retracted upon the request of the author]